Sexual behaviors and awareness of sexually transmitted infections among Chinese university students - Dangui Zhang; Hui Pan; Binglin Cui; Frieda Law; Jeremy Farrar; William Ba-Thein (Journal of Infection in Developing Countries)
Introduction: This study investigated the current state of attitudes, behaviors, and knowledge concerning sex and sexually transmitted infections (STIs) among Chinese university students. Methodology: A cross-sectional anonymous university intranet-based survey was given to students attending the Shantou University, Guangdong, China using a 28-item questionnaire. Results: Of 3425 website visitors, 1030 university students completed the survey, of which 80% were between 20 and 25 years of age, 76% considered pre-marital sex acceptable, 21% had had sexual intercourse, and 45% of sexually active students had engaged in oral sex, anal intercourse, or sex with strangers. Students had limited knowledge and awareness about common STIs, symptoms, and complications. Three percent of the sexually active students reported having had STIs and another 8% were not sure whether they had or not. Most students had misconceptions about transmission and prevention of STIs. The internet was the main information resource for 76% of students. Conclusions: Despite having more open attitudes and behaviors towards sex, students’ STI knowledge and awareness of STI risks was considerably limited, raising concerns about a likely rise in STI incidence. Prior knowledge of STIs had no significant influence. Targeted educational measures such as online education and counseling via Chinese websites and social media, and the provision of safer sex and STI-related information by health experts to university students are suggested.